An Overview of the Use of Recovered Plasma in the Treatment and Prevention of Covid-19. (Indo-American Journal of Life Sciences and Biotechnology, 2018)
Novel coronavirus disease 2019 (COVID -19) has prompted a reevaluation of the efficacy oftraditional convalescent plasma transfusion (CPT) since no particular antiviral medicines have yet beenauthorized for this virus. Since it has been shown that polyclonal neutralizing antibodies may shorten the durationof viremia, convalescent plasma therapy has been used to treat infectious diseases since the early 1900s.According to the facts we have, (a) is the most important result. Patients in critical care who get convalescentplasma treatment have a lower rate of death. (b). Clinical symptoms improved after receiving convalescentplasma. (c).Following CPT treatment, an increase in neutralizing antibody titers and a loss of SARS-CoV-2 RNAwere seen in almost all patients. In this paper, we explore some of the Convalescent plasma therapy (CPT) for thetreatment of COVID-19: an overview of its background, definition, mechanism of action, production,formulation, and therapeutic applications. Potential Risk, Risk Benefit Analysis, Optimal Dosing, Transfusion,and Convalescent Plasma.